Distribution of Puccinia striiformis f. sp. tritici races and virulence in wheat growing regions of Kenya from 1970 to 2014 - Wamalwa, Mercy; Wanyera, Ruth; Rodríguez Algaba, Julian; Boyd, Lesley A.; Owuoche, James O.; Ogendo, Joshua; Bhavani, Sridhar; Uauy, Cristobal; Justesen, Annemarie Fejer; Hovmøller, Mogens S. (Scientific Societies, 2022)
Stripe rust, caused by the fungal pathogen Puccinia striiformis f. sp. tritici, is a major threat to wheat (Triticum spp.) production worldwide. The objective of this study was to determine the virulence of P. striiformis f. sp. tritici races prevalent in the main wheat growing regions of Kenya, which includes Mt. Kenya, Eastern Kenya, and the Rift Valley (Central, Southern, and Northern Rift). Fifty P. striiformis f. sp. tritici isolates collected from 1970 to 1992 and from 2009 to 2014 were virulence phenotyped with stripe rust differential sets, and 45 isolates were genotyped with sequence characterized amplified region (SCAR) markers to differentiate the isolates and identify aggressive strains PstS1 and PstS2. Virulence corresponding to stripe rust resistance genes Yr1, Yr2, Yr3, Yr6, Yr7, Yr8, Yr9, Yr17, Yr25, and Yr27 and the seedling resistance in genotype Avocet S were detected. Ten races were detected in the P. striiformis f. sp. tritici samples obtained from 1970 to 1992, and three additional races were detected from 2009 to 2014, with a single race being detected in both periods. The SCAR markers detected both Pst1 and Pst2 strains in the collection. Increasing P. striiformis f. sp. tritici virulence was found in the Kenyan P. striiformis f. sp. tritici population, and different P. striiformis f. sp. tritici race groups were found to dominate different wheat growing regions. Moreover, recent P. striiformis f. sp. tritici races in East Africa indicated possible migration of some race groups into Kenya from other regions. This study is important in elucidating P. striiformis f. sp. tritici evolution and virulence diversity and useful in breeding wheat cultivars with effective resistance to stripe rust.